Advanced vibration isolation technique using versatile electromagnetic shunt damper with tunable behavior. (1st September 2021) - Li, Jin-Yang; Zhu, Songye
Highlights: EMSD-VNIC can emulate various mechanical dampers by altering external circuit only. Isolation performances of four representative types of EMSD are investigated. Different types of EMSDs show complementary vibration isolation performance. Satisfactory agreement between analytical and experimental results were observed. Abstract: Electromagnetic shunt damper (EMSD) is an emerging damper type capable of mimicking conventional mechanical dampers using their electrical circuit counterparts. Damping, stiffness, and inertance within mechanical domain can be emulated by resistance, inductance, and capacitance from electrical domain, respectively. In particular, four representative conventional damper types, namely, viscous fluid damper (VFD), viscoelastic damper (VED), inerter damper (ID), and tuned inerter damper (TID), are emulated by an EMSD in this paper, thereby forming EMSD-VFD, EMSD-VED, EMSD-ID and EMSD-TID, respectively. Their control performances when installed in a vibration isolation system are subsequently studied both analytically and experimentally. The behavior of EMSD can be easily tuned by changing the external circuits connected to the electromagnetic damper. Moreover, these four types of EMSDs possess complementary isolation performances across the frequency spectrum, which implies that different optimal circuits should be selected in different frequency bands to achieve the best isolation performance. A broadband vibration isolation technique by automatically switching among sub-circuits integrated in a single circuit board will be a promising future research direction.